Análise Clínica, Histopatológica E Do Perfil Inflamatório De Pacientes Portadores De Rinossinusite Crônica Com Polipose Nasal Em Um Hospital Universitário Terciário Do Centro-Oeste Do Brasil - Rodrigues, Stela Oliveira (2024)
Introduction: Chronic rhinosinusitis (CRS) is a disease with several clinical manifestations and endotypic characterization is widely studied for better therapeutic planning. The understanding of the profile of service patients is essential for better management. We aimed to elucidate the clinical and histopathological profile of patients with CRS with nasal polyps (CRSwNP) followed up at a tertiary hospital in the Brazilian Midwest, classifying them according to the predominance of inflammatory response. Methods: Patients with CRSwNP at the Hospital das Clínicas of the Federal University of Goiás were analyzed, trough the application of tomographic and endoscopic scores, clinical control of the disease, in addition to performing prick-test, biopsy of polyps (for histopathological analysis) and collection of epidemiological data. Furthermore, data from literature about the characteristics of the eosinophilic inflammatory response (type 2 pattern) were collected. Results: In descriptive analysis, a predominance of eosinophilic infiltration was observed in middle-aged patientes, with a majority of males, with comorbidities of asthma, allergic rhinitis and atopic dermatitis. There were no significant correlations between eosinophilia and the other data analyzed for each patient. In our systematic review, the main cytokines involved in the type 2 responde were highlighted. Conclusion: In the epidemiological evaluation of patients with CRS at the Hospital das Clínicas, we found a higher prevalence of eosinophilic infiltration, without significant correlations with other epidemiological data, similar to those found in the literature. The cytokines most involved in the type 2 response pattern in nasal polyposis are interleukin (IL)-4, IL-5 and IL-13.